Single droplet size and volume measurement – comparison between experiment and theory - Illias, Suhaimi; Hussain, Suhaila; Ishak, Mohamad Shaiful Ashrul; Abdul Rahman, Md. Tasyrif; Awang @ Hasyim, Syamsul Syahrun; Selamat, Salsuwanda; Ani, Mohd Hanafi (Penerbit UiTM (UiTM Press), Universiti Teknologi MARA, 2023)
The main objective of this paper is to conduct a manual drop test experiment to investigate the actual size and volume of a single droplet. Both experimental result and theoretical value were calculated for comparison. In this study methanol was chosen as the test liquid. The drop test was repeated numerous times with the droplet size measurement being calculated for every 50, 100 and 150 drops. A digital weight measurement was used to precisely measure the droplet weight in the drop test. Meanwhile for theoretical calculation, measurement was made based on chemical properties of the liquid itself. Based on the comparison, it was found that the experimental measurement of droplet size and volume is comparable with the theoretical calculation.